The effect of nitrogen gas flow rate on the properties of tin-coated high-speed steel (HSS) using cathodic arc evaporation physical vapor deposition (PVD) technique - 211479 Mubarak Ali (Skudai : Universiti Teknologi Malaysia, 2005)
PSZJBL